HIV-associated CD4+/CD8+ depletion in infancy is associated with neurometabolic reductions in the basal ganglia at age 5 years despite early antiretroviral therapy. (1st June 2016) - Mbugua, Kenneth K.; Holmes, Martha J.; Cotton, Mark F.; Ratai, Eva-Maria; Little, Francesca; Hess, Aaron T.; Dobbels, Els; Van der Kouwe, Andre J.W.; Laughton, Barbara; Meintjes, Ernesta M.
Abstract : Objective: Investigating consequences of early or late antiretroviral therapy (ART) initiation in infancy on young brain development using magnetic resonance spectroscopy. Design: Most pediatric HIV/ART-related neurological studies are from neuropsychological/clinical perspectives. Magnetic resonance spectroscopy can elucidate the mechanisms underpinning neurocognitive outcomes by quantifying the brain's chemical condition through localized metabolism to provide insights into health and development. Methods: Basal ganglia metabolite concentrations were assessed in thirty-eight 5-year-old HIV-infected children previously participating in a randomized trial comparing early limited ART to deferred continuous ART, as well as 15 uninfected controls (12 HIV exposed). Metabolite levels were compared between 26 infected children who initiated ART at/before 12 weeks and 12 who initiated afterward, and were correlated with clinical HIV and treatment-related measures. Results: HIV-infected children initiating ART after 12 weeks had lower creatine, choline and glutamate ( P  < 0.05) than those initiating ART at/before 12 weeks. The CD4 + /CD8 + ratio at baseline correlated with N-acetyl-aspartate ( r  = 0.56, P  = 0.003) and choline ( r  = 0.36, P  = 0.03) at 5 years, irrespective of treatment regimen and ART interruption. In comparison with uninfected controls, 80% of whom were HIV-exposed in utero, children on early treatment had higher N-acetyl-aspartate ( P  = 0.006) and choline ( P  = 0.03). Conclusions: Despite early ART (<12 weeks), low baseline CD4 + /CD8 + predicts brain metabolite levels in later childhood. Also, HIV exposure and antiretroviral exposure for preventing vertical HIV transmission may hinder metabolite health, but needs further investigation.